The Effect of Government-Borne Final Income Tax Incentives on the Compliance of MSMEs Taxpayers During the Covid-19 Pandemic in Badung Regency - N M Ayu Sumia Dewi; I W Karmana; I W Purwanta Suta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
The Covid-19 pandemic has had an impact on the decline in MSME income. Final income tax incentives borne by the government is one of the government's efforts in the field of taxation. This study aims to determine the effect and magnitude of the effect of the Government's Final Income Tax Incentive on MSME taxpayer compliance during the Covid-19 pandemic in Badung Regency. The questionnaire was used as a data collection tool and the sample used was 95 corporate MSME taxpayers. The focus of this study is the final income tax incentives borne by the government that will apply in 2020 as regulated in the Minister of Finance Regulation starting from PMK 44/2020, PMK 86/2020 to PMK 110/2020 and undergoing several changes and time extensions until PMK 86/2021 which is valid until the end of 2021. The conclusions of this study are (1) The final income tax incentives borne by the government have a positive and significant effect on MSME taxpayer compliance; (2) The final income tax incentive borne by the government has an effect of 23.9% on MSME taxpayer compliance.